The Image of Personal Future in High School and College Students - A.D. Andreeva (Moscow State University of Psychology and Education, 2022)
The article is devoted to the analysis of empirical data on the structure and content of the image of personal future among high school and junior college students. The study was carried out using the method of prototypical analysis of free associations by P. Verges, developed in line with the concept of social representations by S. Moscovici. The hypothesis was tested that the respondents' image of the future will be different depending on their gender and level of education. The study involved junior college students (153 people) and students of grades 10-11 of secondary schools in Moscow, Chelyabinsk and Orsk (191 people). It is established that the aspiration to the future still remains the leading psychological characteristic of adolescence, and the expressed optimism of the personal future image is interpreted as a predictor of readiness to overcome the crisis of self-determination. Gender differences in the structure and content of the personal future image are manifested in the orientation of young men mainly to professional self-realization, while for young women family and the emotional comfort associated with it are more important. The educational status of respondents also influences the content of the psychological image of personal future. Schoolchildren are distinguished by pronounced immaturity, naivety and cliched social ideas about their adult life, while college students show a somewhat more realistic picture.